Physiological intensity of exercises of table tennis that are used on students' lessons in technical higher institute - Buren N.V.; Rovny A.S. (Fizičeskoe Vospitanie Studentov, 2012)
The results of research of physiological intensity of exercises of table tennis are presented. 36 students of basic group took part in research (age 17-19 years). Exercises were used with a ball and racket, teaching applied on the initial stage. Registration of frequency of heart-throbs was carried out each 5 seconds by the monitor of cardiac rhythm of Garmin Forerunner 305. The reactions of the cardiovascular system of organism of students and indexes of intensity of loading are certain. Classification of exercises is offered on the level of coordinating complication. The orientation of loading and its dependence is analysed on coordinating complication of motive task. It is set that physiological intensity of exercises of table tennis with the «low» and «middle» level of coordinating complication is characterized the aerobic orientation of loading.